Electronic initiatives as a tool for e-democracy: the experience of Ukraine and Latvia - Luchenko, D. V. (Problems of legality, 2021)
The article is devoted to a comparative legal analysis of the experience of Ukraine and Latvia in the implementation of the institution of electronic initiative as an important tool of direct e-democracy. The practical question of why in some countries e-initiatives are a real leverage, while in others it is more likely just a marker that signals certain problems of concern to society, prompts a thorough study of legal regulation and information technology support of e-initiatives. For a comparative analysis of the regulation of the procedure for submitting and considering an electronic initiative, the experience of Latvia as a state that has demonstrated real successful results of the work of the online platform ManaBalss.lv as a tool for presenting, registering, discussing, considering an electronic initiative and solving issues in it was selected. In addition, the experience of this country shows that an increase in the level of participation of citizens in the management of public affairs is possible provided they are provided with an effective and convenient mechanism of influence. The article focuses on the shortcomings of the legal regulation of the institution of electronic petitions in Ukraine as the main factor in the ineffectiveness of this tool of e-democracy, including the absence of a special legislative act on electronic petitions, a legislative guarantee for resolving the issue that is raised in the petition, failure to take into account public opinion, expressed in a petition that received fewer votes than is required by law, etc. The necessity of introducing a mechanism for preliminary verification of the content of electronic petitions for constructiveness, reliability and reality is indicated. It is noted that for the proper implementation of the goal of direct e-democracy, levers of influence on the government must be created, which will make it listen to the problems of public concern.